Obtaining simultaneously high crystallinity and sub-bandgap absorption in femtosecond laser hyperdoped black silicon using ion beam etching - Simon Paulus; Patrick Mc Kearney; Friedemann Völklein; Stefan Kontermann (AIP Advances, 2021)
Femtosecond laser sulfur hyperdoped silicon (fs-hSi) is capable of absorbing photons in the infrared spectral range while simultaneously exhibiting negligible reflection. However, laser processing creates detrimental amorphous and polycrystalline silicon surface layers impairing electronic properties, especially reducing minority charge carrier lifetimes. This paper demonstrates how to selectively remove these disadvantageous layers by ion beam etching, while crystalline IR-absorbing silicon underneath is left. The increase in silicon crystallinity is quantified by laterally probing the fs-hSi samples with Raman spectroscopy.